Journal of Occupational Medicine and Toxicology - Groneberg, David; Fischer, Axel
The Journal of Occupational Medicine and Toxicology (JOMT) is a multi-disciplinary journal focussed on clinical and scientific aspects of occupational and environmental health. The field is devoted to the diagnosis, prevention, management and scientific analysis of occupational diseases, injuries and disability. It also covers the promotion of health of workers, their families, and communities, and ranges from rehabilitation to tropical medicine and public health aspects. As an open access, peer-reviewed journal, JOMT offers a platform for both clinicians and researchers in the wide-ranging discipline of occupational medicine and toxicology.